Microglia and Perivascular Macrophages Act as Antigen Presenting Cells to Promote CD8 T Cell Infiltration of the Brain - Goddery, Emma N.; Fain, Cori E.; Lipovsky, Chloe G.; Ayasoufi, Katayoun; Yokanovich, Lila T.; Malo, Courtney S.; Khadka, Roman H.; Tritz, Zachariah P.; Jin, Fang; Hansen, Michael J.; Johnson, Aaron J. (Frontiers in Immunology, 2021)
CD8 T cell infiltration of the central nervous system (CNS) is necessary for host protection but contributes to neuropathology. Antigen presenting cells (APCs) situated at CNS borders are thought to mediate T cell entry into the parenchyma during neuroinflammation. The identity of the CNS-resident APC that presents antigen via major histocompatibility complex (MHC) class I to CD8 T cells is unknown. Herein, we characterize MHC class I expression in the naïve and virally infected brain and identify microglia and macrophages (CNS-myeloid cells) as APCs that upregulate H-2Kb and H-2Db upon infection. Conditional ablation of H-2Kb and H-2Db from CNS-myeloid cells allowed us to determine that antigen presentation via H-2Db, but not H-2Kb, was required for CNS immune infiltration during Theiler’s murine encephalomyelitis virus (TMEV) infection and drives brain atrophy as a consequence of infection. These results demonstrate that CNS-myeloid cells are key APCs mediating CD8 T cell brain infiltration.